Periosteal distraction osteogenesis versus immediate periosteal elevation in a rat model: Histological and micro-CT analysis. Issue 5 (May 2017) - Nakahara, Ken; Haga-Tsujimura, Maiko; Sawada, Kosaku; Mottini, Matthias; Schaller, Benoit; Saulacic, Nikola
Abstract: Purpose: The aim of the present study was to compare periosteal distraction osteogenesis (PDO) to immediate periosteal elevation (IPE) in terms of de novo bone formation. Material and methods: Animals of PDO Group were subjected to a 7-day latency period and a 10-day distraction period. Distraction device in IPE Group were activated for 1 mm at placement. Both groups of animals were euthanized at 17, 31 and 45-day following surgery and the samples analyzed histologically and by micro-CT. Total gap region (TG) was divided in two subregions, less than 0.5 mm (LG) and over 0.5 mm of the gap height (HG). Results: Bone formation in PDO Group was observed in the distal region of the distraction gap, whereas in IPE Group proximally and distally from the distraction gap. Bone volume increased in both groups in LG, HG and TG (p < 0.001), while bone mineral density only in HG (p = 0.001). More new bone was observed in PDO than in IPE Group in HG (p = 0.017) and in TG (p < 0.001), without differences found in bone mineral density. Conclusions: The function of immediately elevated periosteum is limited to the distance to the underlying bone. PDO may be successfully applied to maintain the osteogenic capacity of elevated periosteum.